Multiple prevalent fractures in relation to macroscopic bone architecture in patients with cystic fibrosis - Stahl, Mirjam; Holfelder, Christian; Kneppo, Carolin; Kieser, Meinhard; Kasperk, Christian; Schönau, Eckhard; Sommerburg, Olaf; Tönshoff, Burkhard (Journal of cystic fibrosis, 2018)
Background - The relative risk for bone fractures in patients with cystic fibrosis (CF) and its relationship to macroscopic bone architecture assessed by pQCT and DXA are incompletely defined. - Methods - In a cross-sectional study of 43 CF patients (age, 17.8±6.2years), rate and location of fractures, bone mass, density, geometry, and strength of the radius as well as forearm muscle size were investigated. - Results - The fracture rate in CF was 9.2-fold higher compared to an age-matched German control population. The probability of remaining free of any fracture in CF patients at 25years was reduced to 39.8% compared to 84.6% in controls (P<0.001). Assessment of macroscopic bone architecture by DXA and pQCT allowed the differentiation of patients with multiple prevalent fractures with a high sensitivity (up to 100%) and specificity (up to 94.3%). - Conclusions - Bone densitometry is a useful tool for noninvasive assessment of fracture risk in CF patients.
Gesehen am 04.11.2019